Prepectoral implant pocket conversion in breast reconstruction. (December 2020) - Mangialardi, Maria Lucia; Salgarello, Marzia; Baldelli, Ilaria; Raposio, Edoardo
Abstract: Introduction: While many authors have reported their experience in immediate prepectoral breast reconstruction (BR), implant pocket conversion from a submuscular to a prepectoral plane is less well described. The aim of this study is to provide a comprehensive review on plane conversion in implant-based BR, including the indications, surgical techniques, functional, and esthetic results. Materials and Methods: A literature search via PubMed, Medline, Google Scholar, and Cochrane databases was performed using the following MeSH terms: "prepectoral pocket conversion", "subcutaneous pocket conversion", "prepectoral plane conversion", "subcutaneous plane conversion", and "prepectoral breast reconstruction". Results: Ten articles in which 504 breasts were studied were deemed eligible for inclusion. The indications to perform plane conversion were animation deformity (AD), chronic pain, and implant malposition. Seven studies described complete or partial capsulectomy. The use of acellular dermal matrices (ADM) was reported in all cases except for three studies. The mean follow-up was 10.64 months. There was resolution of AD in 100% of cases. Three studies reported complete resolution of chronic pain. The overall complication rate was 12.102% and capsular contracture (CC) was the most frequent complication. Cosmetic revisions were reported in six studies (9.52%). The use of ADMs and fat grafting appeared to decrease the rate of subsequent CC formation and cosmetic revisions. Conclusions: The current article represents the first review about implant pocket conversion from a submuscular to a prepectoral plane, delineating its indications, surgical technique, postoperative complications, and functional and esthetic outcomes.